Measurement of the ratio of branching fractions of the decays [lambda] 0b→[psi] (2S) [lambda] and [lambda] 0b→J/[psi lambda] - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2019)
Using pp collisions corresponding to 3 fb−1 integrated luminosity, recorded by the LHCb experiment at centre-of-mass energies of 7 and 8 TeV, the ratio of branching fractions B(Λ0b→ψ(2S)Λ)/B(Λ0b→J/ψΛ)=0.513±0.023(stat)±0.016(syst)±0.011(B)B(Λb0→ψ(2S)Λ)/B(Λb0→J/ψΛ)=0.513±0.023(stat)±0.016(syst)±0.011(B) \mathrm{\mathcal{B}}\left({\Lambda}_b^0\to \psi (2S)\Lambda \right)/\mathrm{\mathcal{B}}\left({\Lambda}_b^0\to J/\psi \Lambda \right)=0.513\pm 0.023\left(\mathrm{stat}\right)\pm 0.016\left(\mathrm{syst}\right)\pm 0.011\left(\mathrm{\mathcal{B}}\right) is determined. The first uncertainty is statistical, the second is systematic and the third is due to the external branching fractions used. Open image in new window
Gesehen am 16.07.2019
Die 0 ist im Titel hochgestellt, das b ist tiefgestellt
Im Titel werden Lambda und psi als griechische Buchstaben dargestellt